Answer:
+ 9
+ 8
<em><u>(This is an expression, not an equation so you can't find x with this expression. Equations have an = sign which can help isolate x on one side to find the value of x. This is the closest thing you could do for an answer for this expression.)</u></em>
Step-by-step explanation:
x(x+1)+(x+1)(x+2)+(x+2)(x+3)
= (x)(x) + (x)(1) + (x)(x) + (x)(2) + (1)(x) + (1)(2) + (x)(x) + (x)(3) + (2)(x) + (2)(3)
= <em>x^2</em> + x + <em>x^2</em> + 2x + x+ <u>2</u> + <em>x^2</em> + 3x + 2x + <u>6</u>
= (<em>x^2+x^2+x^2</em>) + (x+2x+x+3x+2x) + (<u>2+6</u>)
=
+ 9
+ 8
So first you expand the brackets and then you combine like terms.